Stesen Penyelidikan MPOB Sessang / Mohamad Nurhafizi Nasir - Nasir, Mohamad Nurhafizi (Universiti Teknologi MARA, Sarawak, 2016)
The Malaysian Palm Oil Board (MPOB) is a government agency responsible for the promotion and development of the palm oil industry in Malaysia.MPOB is one of agencies under Malaysia's Ministry of Plantation Industries and Commodities. The Malaysian Palm Oil Board (MPOB) was established in 1998 with the passing of the Malaysian Palm Oil Board Act, which led to the merger of two pre-existing agencies, the Palm Oil Research Institute of Malaysia (PORIM) and the Palm Oil Registration and Licensing Authority (PORLA). The resulting organisation was named the Malaysian Palm Oil Board and officially began operations in May 2000. The first Director-General of the MPOB was Yusof Basiron who served until 2006. The MPOB is an agency of the Ministry of Plantation Industries and Commodities and is funded by palm oil industry taxes and through government grants for research. The current chairman is Shahrir bin Abdul Samad, and the director general is Choo Yuen May. According to the organisation's official website, the MPOB is headquartered in Kuala Lumpur and operates additional offices both within Malaysia and abroad, including offices in China, Brussels, Pakistan, the United States and Egypt. The MPOB requires all businesses involved in the palm oil industry to be licensed through the organisation. The organisation's activities include research, publication, development and implementation of regulations and the promotion of the palm oil industry in Malaysia. The MPOB oversees all stages of palm oil production in Malaysia, from planting to exporting. It publishes several journals, including the Journal of Oil Palm Research.